2019
DOI: 10.3390/molecules24224175
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Acetylcholinesterase Activities of Mono-Herbal Extracts and Exhibited Synergistic Effects of the Phytoconstituents: A Biochemical and Computational Study

Abstract: Alzheimer’s disease (AD), a neurodegenerative disease, is the most common form of dementia. Inhibition of acetylcholinesterase (AChE) is a common strategy for the treatment of AD. In this study, aqueous, hydro-methanolic, and methanolic extracts of five potent herbal extracts were tested for their in vitro anti-AChE activity. Among all, the Tinospora cordifolia (Giloy) methanolic fraction performed better with an IC50 of 202.64 µg/mL. Of the HPLC analyzed components of T. cordifolia (methanolic extract), palma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results show that the biological activities of the positive controls in this study are comparative to the previously published values [ 56 , 57 , 58 ]. On the other hand, the experimental assays also specified that AC12 had a higher activity than galantamine on AChE and all the synthesized chalcones exhibited the higher inhibiting effects than quercetin on BACE-1.…”
Section: Resultssupporting
confidence: 53%
“…The traditional medicinal system is based on the application of polyherbal formulations. Pharmacological effects obtained from multiple plant extract metabolites are much higher as compared to single herb extracts (Yadav et al, 2008;Balkrishna et al, 2019a). In modern medicine, the treatment for chronic diseases has shifted from the "one drug, one target, one disease" paradigm toward combination therapies (Williamson, 2001;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%